Fetal cervical lymphangioma: prenatal diagnosis and perinatal out-come - Saenz, Igor Huerta (2013)
A case of fetal cervical lymphangioma is reported, tumor of infrequent presentation and potential perinatologic emergency in relation to superior fetal airways compromise. Ultrasound and nuclear magnetic resonance are the main tools to establish diagnosis and perinatal prognosis of fetuses carrying cervical lymphangioma as well as other cervical tumors. EXIT procedure coordinated with a multidisciplinary equipment must be planned in cases when the fetus displays a high risk of upper airway obstruction.